Potensi Ekosistem Mangrove untuk Mewujudkan Kawasan Pesisir Berkelanjutan di Desa Wedung, Kecamatan Wedung, Kabupaten Demak, Jawa Tengah - Cahyo Wulandari; Nofika Tri Kusuma Hapsari; Dhimas Wahyu Putranto; Tsabita Umniyyatina Syahid (Direktorat Pengabdian kepada Masyarakat, 2023)
In the context of promoting sustainable development, coastal areas play a pivotal role in supporting local communities, as the region's economic activities heavily rely on its natural resources. One such coastal village is Wedung Village, situated in Wedung District, Demak Regency, Central Java. With its extensive coastal expanse, this area holds immense potential in terms of natural resources. The local community has undertaken various initiatives to harness these resources, including the establishment of shrimp and fish ponds, along with the utilization of diverse mangrove products. The significance of mangrove ecosystems in upholding the coastal equilibrium cannot be understated. However, these mangroves are currently confronted by an escalating threat of degradation due to land clearance for aquaculture ponds. This article centers on a community service program, specifically the development of the mangrove ecosystem's potential as part of the 2023 UGM Community Service Program-PPM (KKN-PPM) in Wedung Village, Demak. A range of programs aimed at tapping into the mangrove ecosystem's potential have been devised, encompassing education on the advantages and ecological importance of mangroves, mangrove ecosystem learning for students, mangrove distribution mapping, guidance on silvofishery practices, and the planting of mangrove saplings. The methodology employed involves a blend of literature review, on-site observations, and community engagement. Data collection done by direct observation and interviews with mangrove advocates and community leaders. The collected information is qualitatively and descriptively analyzed to perceive the potential of the mangrove ecosystem. From the data, Wedung Village had shown remarkable potential on mangrove ecosystems. The implementation of silvofishery practices emerges as a means to preserve the ecological role of mangroves and enhance aquaculture productivity. In addition, mangrove seedlings were planted as a form of conservation efforts. These initiatives have effectively heightened community awareness regarding the significance of mangroves and their sustainable stewardship.